Utilization of Dilalah Lafzhiyah's Notion Inside the Hanafiyyah Perspective in the Domain of Family Law - Aldy Darmawan; Zainal Azwar (WARAQAT : Jurnal Ilmu-Ilmu Keislaman, 2023)
This study examines Hanafiyyah's perspective on dilalah lafzhiyah in family law, categorizing Lafadz into ibarah nash, isyarah nash, dilalah nash, and iqtidha' nash. Through library research, it explores the implementation of dilalah lafzhiyyah, focusing on Q.S. An-Nisa verse 3, permitting multiple marriages under fair conditions, and Q.S. Al-Baqarah verse 233, outlining the husband's responsibility for sustenance during the 'iddah period. Inheritance laws, as per Q.S. An-Nisa' verse 11, allocate shares based on heirs' presence and, if parents are the only heirs, assign the mother one-third. Dilalah, ghairu lafzhiyyah involves deriving legal principles from implicit implications within explicit language, derived from the lafazh.